Construct validation and intra-rater reproducibility of the 6-minutes step test in healthy children aged 7-11 years (Research, Society and Development, 2021)
Objective: To validate the six-minute step test (6MST) and evaluate its reproducibility for determining exercise tolerance in healthy children aged 7-11 years. Methods: 66 healthy children, aged between 7 and 11 years old, were included in the research. The volunteers underwent the six-minute walk test (6MWT) and the 6MST. Results: A moderate positive correlation was observed between the distance covered on the 6MWT and the number of climbs on the 6MST (r = 0.43; p